1984
DOI: 10.1021/bi00299a029
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the actin-activated adenosine triphosphatase activity of myosin by tropomyosin from vascular and gizzard smooth muscles

Abstract: Tropomyosins from bovine aorta and pulmonary artery exhibit identical electrophoretic patterns in sodium dodecyl sulfate but differ from tropomyosins of either chicken gizzard or rabbit skeletal muscle. Each of the four tropomyosins binds readily to skeletal muscle F-actin as indicated by their sedimentation with actin and by their ability to maximally stimulate or inhibit actin-activated ATPase activity at a molar ratio of one tropomyosin per seven actin monomers. Smooth and skeletal muscle tropomyosins diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The activation in the presence of Ca2" was similar even though TM isoforms often differ quantitatively with regard to this phenomenon (29,41). The state of the thin filament or the ability of the myosin S1 to influence the state of the thin filament does not seem to be affected by the identity of TM exons 2 and 9.…”
Section: Discussionmentioning
confidence: 96%
“…The activation in the presence of Ca2" was similar even though TM isoforms often differ quantitatively with regard to this phenomenon (29,41). The state of the thin filament or the ability of the myosin S1 to influence the state of the thin filament does not seem to be affected by the identity of TM exons 2 and 9.…”
Section: Discussionmentioning
confidence: 96%
“…The calcium sensitivity of the smooth muscle actin-myosin ATPase and tension in skinned fibres was reported to be reduced by a decrease in pH (Mrwa, Achtig & Riiegg, 1974), though recent reports appear to limit the generality of this finding (Jino, 1981;Sparrow, Pfitzer, Gagelmann & Ruegg, 1984;Yamaguchi, Ver, Carlos & Seidel, 1984;Arheden, Arner & Hellstrand, 1989). In this and previous work (Ishida et al 1984) it was shown that a 10-fold increase in glucose under hypoxic conditions elevated lactate content and lactate production while at the same time elevating the level of isometric force.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in some smooth muscles, opposite pH effects on maximum tension were observed (Spurway and Wray, 1987;Smith et al, 1998). For cardiac muscle and smooth muscle, troponin C (Ding et al, 1996) and tropomyosin (Yamaguchi et al, 1984), respectively, were considered as pH sensors, which influence actin-myosin interaction.…”
Section: Atp Step Experimentsmentioning
confidence: 99%